The impact on customer satisfaction towards robotic service in Indian Muslim restaurants/ Mohd Zool Fadli Ibrahim ... [et al.] - Ibrahim, Mohd Zool Fadli; Mohd Amran, Nur Wafiqah; Mohamad Saber, Joesri; Bahari, Khairil Anuar; Johari, Noorsa Riza (Universiti Teknologi MARA, Sabah, 2024)
This study investigates customer satisfaction with service robots in the restaurant industry, focusing on Penang, Malaysia. It begins by exploring the adoption of innovative robotic technologies in the food and beverage sector and traces their evolution over time. The research also examines the benefits and drawbacks of implementing service robots in modern restaurant environments. According to the Department of Statistics Malaysia, Penang had a population of 1.77 million in 2021. A minimum sample size of 385 respondents was determined using Raosft.com, which was selected for its accuracy in sample size estimation. A quantitative research approach was utilised, with data converted into numerical form for subsequent analysis. The study employed SPSS software due to its reliability, widespread use among researchers and institutions, and ability to provide accurate results through a user-friendly interface. The research aims to assess how service robots influence customer acceptance in the restaurant context. By analysing factors impacting customer satisfaction with these robotic services, the study seeks to provide insights into enhancing their adoption and usage. The findings highlight that understanding the elements that affect customer satisfaction is crucial for promoting the continued use of service robots. This understanding is vital for ensuring the sustained development and integration of robotic services within the food and beverage industry. Addressing the identified factors can ultimately contribute to the growth and acceptance of robotic technologies in restaurant settings, facilitating their role in the evolving food service landscape.